The Use of Smartphone for Bipolar Disorder Patients: A Systematic Review - Ruliyani Manumba; Tuti Afriani (Poltekkes Kemenkes Palu, 2023)
Bipolar is a mood disorder characterized by extreme swings between feelings of happiness and sadness. Based on WHO data, around 60 million people experience bipolar disorder. Bipolar disorder causes functional, psychosocial functioning, quality of life impairments and even the risk of suicide. The large number of smartphone users and the increasing computing power of mobile devices can be used as a reference in using smartphones for bipolar disorder. This systematic review aims to determine the use of smartphones for patients with bipolar disorder. The systematic review method was applied to search articles in electronic databases such as PubMed, Science Direct, and SpringerLink published in 2017-2021. The keywords used in the search were